(untitled) (Pedagogy of Higher and Secondary Education, 2003)
The article investigates the problem of combining didactic theories with the concept of effective teaching. It has been shown that this combination contributes a lot to both quality of education and raising the scientific lives of theoretical and teaching manuals.